The Long-Term Effects of In-Utero Exposure to Rubella - Irene Mosca; Anne Nolan (Institute of Labor Economics (IZA), 2022)
A large body of research in economics and other disciplines considers the role of early-life circumstances in shaping later-life outcomes. The foetal origins hypothesis establishes that certain health conditions in later adulthood can be linked to in-utero development. In this paper, we contribute to the evidence on the foetal origins hypothesis by examining the later-life impact of a rubella outbreak that occurred in Ireland in 1956. Rubella is a contagious viral disease that displays mild symptoms and is generally inconsequential in childhood or adulthood. However, a rubella infection in early pregnancy poses a significant risk of damage to the foetus. Matching the outcomes of individuals born in 1955 to 1958 who are in the 2016 Irish Census to the county-level rubella incidence rate that was prevailing when respondents were in utero, we find that a 1% increase in the rubella incidence rate when in utero is associated with a 0.03% to 0.17% increase in the probability of having lower levels of educational attainment, being in poor health and having a disability in later life.
Keywords: I10; I18; J13; 330; in-utero; rubella; Ireland; later-life health